Growth of BaSi2 continuous films on Ge(111) by molecular beam epitaxy and fabrication of p-BaSi2/n-Ge heterojunction solar cells. (20th February 2017) - Takabe, Ryota; Yachi, Suguru; Tsukahara, Daichi; Toko, Kaoru; Suemasu, Takashi
Abstract: We grew BaSi2 films on Ge(111) substrates by various growth methods based on molecular beam epitaxy (MBE). First, we attempted to form BaSi2 films directly on Ge(111) by MBE without templates. We next formed BaSi2 films using BaGe2 templates as commonly used for MBE growth of BaSi2 on Si substrates. Contrary to our prediction, the lateral growth of BaSi2 was not promoted by these two methods; BaSi2 formed not into a continuous film but into islands. Although streaky patterns of reflection high-energy electron diffraction were observed inside the growth chamber, no X-ray diffraction lines of BaSi2 were observed in samples taken out from the growth chamber. Such BaSi2 islands were easily to get oxidized. We finally attempted to form a continuous BaSi2 template layer on Ge(111) by solid phase epitaxy, that is, the deposition of amorphous Ba–Si layers onto MBE-grown BaSi2 epitaxial islands, followed by post annealing. We achieved the formation of an approximately 5-nm-thick BaSi2 continuous layer by this method. Using this BaSi2 layer as a template, we succeeded in forming a -axis-oriented 520-nm-thick BaSi2 epitaxial films on Ge substrates, although (111)-oriented Si grains were included in the grown layer. We next formed a B-doped p-BaSi2 (20 nm)/n-Ge(111) heterojunction solar cell. A wide-spectrum response from 400 to 2000 nm was achieved. At an external bias voltage of 1 V, the external quantum efficiency reached as high as 60%, demonstrating the great potential of BaSi2 /Ge combination. However, the efficiency of a solar cell under AM1.5 illumination was quite low (0.1%). The origin of such a low efficiency was examined.